University Art History in Slovakia after WWII and its Sovietization in 1950s - Kolbiarz Chmelinová, Katarina (Artium Quaestiones, 2019)
In post-WWII Slovakia, art history was available only as a university field of study at Bratislava University (in 1954 regaining its name Comenius University) at the Seminár pre dejiny umenia / Seminar of Art History, a separate part of the Faculty of Arts of the university, where art history had been taught as an independent discipline since 1923 before its conversion to a department. Post-war changes in state structures and the new political system radically affected Slovak society and the education system in the country. This article is the very first attempt to present in detail the extent and character of changes in university art history instruction in the part of the socialist era of the Czechoslovak Republic. It is based on the study and comparison of previously unprocessed sources from various university and state archives and their classification in the context of known historical facts. This contribution represents an in-depth probe into the post-war efforts to build a new university foundation and system of art history instruction in Slovakia within the Czechoslovak Republic, and its Sovietization as well. The text analyzes the university environment, the curriculum, the study program of art history and the relevant changes resulting from political pressure from 1945 to 1960. They were the consequence of two directly related, significant moments in the history of Slovakia: the establishment of the Third Czechoslovak Republic in 1945 and the communist coup in 1948, which was followed by the most totalitarian period in the history of the state. The article also discusses the personal changes in the art history staff forced by the political situation (J. Dubnický, V. Wagner, V. Mencl, A. Güntherová-Mayerová, R. Matuštík, T. Štrauss, K. Kahoun). After a brief presentation of the situation in Czechoslovakia at the time, the article first deals with the ad hoc activities and efforts of scientists seeking to maintain art history studies in Slovakia at the university level immediately after the end of the war. The central issue in the article is the changes in the way of teaching resulting from the political upheaval in February 1948. Against the background of political and social changes, the new law on higher education (Act No. 58/1950), which forces significant organizational transformations, is discussed. As part of the process of Sovietization of university education in Slovakia, the modified Seminar of Art History lost its independent status for a long time, and its staff was largely replaced. At the same time, throughout this period, there was a visible tendency to stabilize the teaching system and attempts to become independent again and to develop discipline, undertaken contrary to the imposed system. The 1950s, with their new rhetoric and propaganda optimism, appear to be a decade devoid of internal consistency. It started the most totalitarian period, which lasted until Stalin’s death in 1953, but was followed by a short thaw and then by a new wave of repression after 1957, which chose victims even at the beginning of the next decade. The article focuses on two sides of the 1950s – centralization and the dominant ideological control of the Communist Party, on one hand, and on the other, the obvious effort to unify and professionalize the teaching of the discipline. The factual material presented here shows the scale of changes interpreted in the context of the political and social changes of that time. The case study provides an analysis of system efforts made in the 1940s and 1950s to establish new principles of university teaching for the history of art in Slovakia as part of the Czechoslovak Republic. It aims to broaden the factual basis and existing overview of knowledge of art history in Slovakia and supplement existing studies on the history of art history in the country (J. Bakoš, I. Ciulisová, B. Koklesová).